Tickets for Household Activities – A Form of Remuneration for Household Providers - Elena STĂNCIULESCU (CECCAR Business Review)

(untitled)
Tickets for household activities are a form of remuneration of household providers. By means of this payment method, household providers acquire the status of insured persons in both the state social insurance system and the health insurance system. Thus, it is important to know the regulations in the field, how these tickets purchased directly by domestic beneficiaries or by means of employers circulate, the obligations of the latter, the exchange procedure, the method of calculating the rights due to household providers , the deductions made, and who has the obligation towards the state to make them. We also need to know the types of activities household providers can perform and how free tickets can be granted.